Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Terhadap Pelaksanaan Ibadah Salat Berjamaah Peserta Didik Kelas VIII di SMP Negeri 8 Palopo - rahma fitri; Bustanul Iman RN; Bungawati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Learning Islamic Religious Education and Character Building plays an important role in shaping students' religious attitudes, including getting used to performing congregational prayers in the school environment. This study aims to analyze the influence of learning Islamic Religious Education and Character Building on the implementation of congregational prayers of eighth grade students at SMP Negeri 8 Palopo. The study used a quantitative approach with a survey design. The study population was 185 students, while a sample of 37 students was selected using a proportional sampling technique. Data were collected through a closed questionnaire with a Likert scale, then analyzed using simple linear regression analysis, t-test, and coefficient of determination (R²) with the help of IBM SPSS version 20. The results showed that the level of learning Islamic Religious Education and Character Building was in the very high category with an average of 36.05 (90.13%), while the implementation of congregational prayers was also in the very high category with an average of 36.03 (90.08%). Regression analysis shows that Islamic Religious Education and Character Education learning has a positive and significant effect on the implementation of congregational prayer (t = 10.746; p < 0.001), with a coefficient of determination of 0.767. This finding indicates that Islamic Religious Education and Character Education learning contributes 76.7% to the implementation of congregational prayer among students.